Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\left(x-3\right)\left(3x+2\right)-3x\left(x-5\right)+3\)
\(=x.\left(3x+2\right)-3.\left(3x+2\right)-3x\left(x-5\right)+3\)
\(=x.3x+x.2-3.3x-3.2-3x.x+3x.5+3\)
\(=3x^2+2x-9x-6-3x^2+15x+3\)
\(=8x-3\)
b )
\(2x\left(x-3\right)-\left(x-5\right)\left(2x-1\right)\)
\(2x.x-2x.3-x.\left(2x-1\right)-5.\left(2x-1\right)\)
\(2x.x-2x.3-x.2x+x.1-5.2x+5.x\)
\(2x^3-6x-2x^2+x-10x+5x\)
\(2x^3-15x-2x^2\)
(3x^3+3x+1)(3^3-3x+1)-(3x^3+1)^2
=3x^3(3^3-3x+1)+3x(3^3-3x+1)+1(3^3-3x+1)-(3x^3)^2+2.3x^3.1+1^2
=3^4x^3-3^2x^4+3x^3+3^4x-3^2x^2+3x+3^3-3x+1-3^2x^6+6x^3+1
=(3^4x^3+3x^3)-(3^2x^4-3^2x^6-3^2x^2)+(3^4+3^3+1+1+1-3^2)+(3x-3x-3x)
=x^3(3^4+3)-3^2(x^4-x^6-x^2)+102-3x
=84x^3-9.(x^4-x^6-x^2)+102-3x
2x(3x3-x)-4x2(x-x2+1)+(x-3x2)x
=6x4-2x2+4x4-4x3-4x2+x2-3x3
=(6x4+4x4)+(-4x3-3x3)+(-4x2-x2)
=10x4-7x3-5x2
\(2x\left(3x^3-x\right)-4x^2\left(x-x^2+1\right)+\left(x-3x^2\right)x\\ =6x^4-2x^2+4x^4-4x^3-4x^2+x^2-3x^3\\ =\left(6x^4+4x^4\right)+\left(-4x^3\right)-3x^3+\left(-4x^2-x^2\right)\)
\(=10x^4-7x^3-5x^2\)
\(\dfrac{3x^2-3x+3}{x^3+1}\)
\(=\dfrac{3\left(x^2-x+1\right)}{\left(x+1\right)\left(x^2-x+1\right)}\)
\(=\dfrac{3}{x+1}\)